A CHANCE OF LEARNING: THE PLAY IN EARLY CHILDHOOD EDUCATION AND EARLY YEARS OF BASIC EDUCATION (Fiep Bulletin - online, 2015)
This study aims to analyze the theoretical concepts about playing in kindergarten and the early years of elementary school. This is a basic survey of the literature reveals that like the importance of using play and their contribution to the development of psychomotor, cognitive and social functioning of the child. We also highlight the important role that the teacher plays in the action of play and the use of games. Given the analysis, we can confirm that the play is of paramount importance to, cognitive, affective, social and psychomotor development of children. We conclude from this study that the game is a source of pleasure while learning, in which children attending early childhood education and early years of elementary school develop many of their potential through this key resource that game.
Keywords: Game Playing; Childhood Education; early years of elementary school.